Venezuela: ¿Autonomía nacional o reproducción de la especificidad? - DACHEVSKY, FERNANDO (CONfines de Relaciones Internacionales y Ciencia Política)
The present work analyzes the international relations of Venezuela during the governments of Hugo Chávez and Nicolás Maduro. We focused on providing an explanation for its growing confrontation with the US government and its rapprochement with countries such as China and Russia. This is a problem that was addressed by numerous studies and on which an alternative approach is proposed here, arguing that the change in the external partners of Venezuela was but a necessary form of continuity in its specificity as a national process of capital accumulation based on the appropriation of income from the oil land.